Epidemiology of traumatic falls after Hurricane Maria in Puerto Rico - Laura Ramírez-Martínez; Mariella Chamah-Nicolás; Mariely Nieves-Plaza; Javier Ruiz-Rodríguez; Pedro Ruiz-Medina; Ediel O. Ramos-Melendez; Pablo Rodríguez-Ortiz (BMC, 2020)
Abstract Background Hurricanes are among the most devastating natural disasters, playing a significant role in public health. Currently, the epidemiology of fall-related injuries after the occurrence of a tropical storm is not well described. This study aims to compare the demographical patterns, clinical profile, hospital course, and costs of patients admitted to the Puerto Rico Trauma Hospital before and after Hurricane Maria. Methods A retrospective study was performed to compare fall-related injuries after the hurricane (September 20, 2017 - January 20, 2018) with a control period (same period in 2014-2016). Comparison between the groups was done using chi-square, Mann-Whitney test, and logistical regression. Results After the hurricane, there was an increase in the proportion of fall-related admissions in subjects aged 40-64 years (39.2% vs. 50.6%) and a decrease among those aged 18-39 years (16.0% vs. 5.9%), when compared with the previous years. A greater proportion of patients presented with work related injuries (3.9% vs. 9.4%). No significant differences were identified for sex, Glasgow Coma Scale, Injury Severity Score, and hospital outcomes (hospital and intensive care unit days, mechanical ventilation, and mortality). Intracranial injuries were marginally higher post-Maria (p = 0.06). In multivariate analysis, during the post-Maria period, an increased risk of fall-related injuries was observed among subjects ≥40 years (OR: 3.20) and injuries related to recovery work (OR: 2.64) (p < 0.05). Conclusions Our study shows that there is an increased risk of fall-related injuries among middle-aged individuals after a hurricane, causing significant changes in epidemiology. This study helps to elucidate the health consequences of falls and, in doing so, improves healthcare preparedness, interventions, and planning for future natural disasters.